The effect of 7E learning cycle enriched with computer animations on students' conceptual understanding and overcoming misconceptions - Zeleke B. Mekonnen; Destaw D. Yehualaw; Solomon M. Mengistie; Baye S. Mersha (Journal of Pedagogical Research, 2024)
While computer animations have the potential to assist learners in understanding difficult concepts and eliminating misconceptions, studies supporting this claim are scarce. This study investigated how the 7E instructional model integrated with computer animations affected students' conceptual understanding and misconceptions about food making and plant growth. Experimental groups were taught the 7E learning cycle model [7E LCM], and 7E LCM with computer animation [CA] while the control group was taught the conventional instruction method. A two-tiered conceptual understanding multiple-choice test and semi-structured interviews were used to collect the data. ANOVA analysis revealed no significant differences between groups or genders in pre-food making and growth in plant conceptual understanding [pre-FMGPCU] and pre-misconceptions test scores [pre-MC]. There were, however, significant differences in post-FMGPCU and post-MC mean scores, with the 7E LCM with CA showing better results in improving conceptual understanding and minimizing misconceptions. MANOVA revealed no statistically significant difference between male and female students' post-FMGPCU and post-MC results. It was concluded that the 7E LCM with CA enhances students' conceptual understanding and minimizes misconceptions more effectively than other instructional approaches. It is recommended that similar designs be used in biology teaching.